Metal sulfide and its application

By controlling the particle size distribution span value and crystal structure of zinc sulfide material, it is applied to brake pad friction materials, and the problem of lowering friction coefficient in extreme environments is solved, and stable braking performance and low wear rate are achieved at high and low temperatures.

CN119320160BActive Publication Date: 2025-03-04IKENS INFRARED TECHNOLOGY (GUANGDONG) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411875710.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-04
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Existing brake pads have reduced friction coefficient in extreme environments (such as high and low temperatures), resulting in unstable braking performance and the addition of lubricant may reduce braking performance.

Method used

By controlling the particle size distribution span value and crystal structure of zinc sulfide material, it satisfies a specific relationship: 0.2≤span×((I1+I3)/I2)≤6.3, it is applied to friction materials to maintain stable braking performance at low and high temperatures.

Benefits of technology

The friction coefficient change rate is small, wear rate is low, and friction stability is significantly improved under low and high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320160B_ABST
    Figure CN119320160B_ABST
Patent Text Reader

Abstract

The present invention discloses a metal sulfide and its application, and relates to the technical field of sulfides. The metal sulfide of the present invention is a zinc sulfide material, and the zinc sulfide material satisfies the following relationship: 0.2≤span×((I 1 +I 3 ) / I 2 )≤6.3; wherein, the span is the particle size distribution span value of the zinc sulfide material; the I 1 ,I 2 ,I 3 The peak intensities of the diffraction peaks at 26.7-27.1°, 28.4-28.8°, and 30.4-30.8° in the XRD spectrum of the zinc sulfide material obtained by XRD measurement are respectively represented. The metal sulfide of the present invention is applied to the friction material, which helps the friction material to have a small change rate of friction coefficient and a low wear rate under extreme environments such as low temperature and high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sulfides, and in particular to a metal sulfide and application thereof. Background Art

[0002] In the automobile braking system, brake pads are a crucial component that directly affects the braking performance and safety of the vehicle. The performance of brake pads is required to meet certain standards in terms of friction coefficient, wear resistance, etc. to ensure that the vehicle braking effect is stable, safe and reliable.

[0003] In the design of brake pads, the friction coefficient is a crucial parameter. Normally, the friction coefficient of ordinary brake pads is about 0.3 to 0.4, while the friction coefficient of high-performance brake pads is between 0.4 and 0.5. For brake pads with a higher friction coefficient, the vehicle only needs to apply less hydraulic pressure (i.e. less pedal force) when braking to generate a greater braking force, thereby achieving a better braking effect. However, if the friction coefficient is high, it means that the surface roughness of the friction material increases, which may cause noise problems. More seriously, it leads to increased friction loss, which makes the material non-wear-resistant and the friction performance deteriorates.

[0004] In order to solve this problem, it is usually considered to add lubricants to reduce friction loss. For example, the prior art CN102713334B discloses a friction material for braking, which includes a lubricant, and the lubricant can be a metal sulfide. However, in actual applications, especially in extreme environments, adding lubricants may reduce the braking performance of brake pads.

[0005] In extreme environments, such as when running at continuous high or low temperatures, the friction coefficient of the brake pads tends to decrease, which in turn affects the braking effect of the vehicle. For example, long-term braking at high speeds will cause the temperature to be too high, causing the friction coefficient of the friction material to drop rapidly; at low temperatures, the friction coefficient may be too low, and the car can only increase the preheating time to allow the brake pads to reach the operating temperature to avoid initial braking failure, which reduces driving safety and comfort. The braking performance of the friction material with the addition of lubricant is further reduced, exacerbating the instability of the braking system in extreme environments. Although the prior art CN 103644228A reports that zinc sulfide can replace resin under hot and humid conditions to play a certain bonding role, it does not solve the problem that the friction coefficient of the brake pads still decreases significantly at higher braking temperatures.

[0006] Therefore, it is necessary to develop a metal sulfide that, when used in friction materials, enables the friction materials to maintain relatively stable braking performance under extreme environments such as low and high temperatures, thereby meeting the high requirements of the braking system for safety, reliability and comfort. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a metal sulfide and its application. By controlling the particle size distribution span value and the crystal structure of the metal sulfide, the metal sulfide can be applied to the friction material. The friction material can maintain stable braking performance under extreme environments such as low temperature and high temperature, and the friction coefficient change rate under high temperature and low temperature conditions is small, and the wear rate is low.

[0008] To achieve the above object, in a first aspect of the present invention, the present invention provides a metal sulfide, wherein the metal sulfide is a zinc sulfide material, and the zinc sulfide material satisfies the following relationship: 0.2≤span×((I1+I3) / I2)≤6.3;

[0009] Wherein, the span is the particle size distribution span value of the zinc sulfide material;

[0010] The I1, I2, and I3 respectively represent the peak intensities of the diffraction peaks at the positions of 26.7-27.1°, 28.4-28.8°, and 30.4-30.8° in the XRD spectrum of the zinc sulfide material obtained by XRD measurement.

[0011] As a metal sulfide, zinc sulfide has certain lubrication properties, which helps to reduce the friction loss of friction materials. However, the existing brake pads with zinc sulfide added, although the friction loss is improved, often cause the braking performance of the brake pads to decrease in extreme environments, especially in low temperature environments, where the friction coefficient decreases significantly.

[0012] The present invention has found that by synergistically controlling the particle size distribution and crystal structure of the zinc sulfide material so that it satisfies the relationship: 0.2≤span×((I1+I3) / I2)≤6.3, the morphology of the zinc sulfide particles is comprehensively regulated from a macroscopic and microscopic perspective, so that the friction material containing the metal sulfide has a higher friction coefficient and lower friction loss under both high and low temperature environments.

[0013] In the above relationship, I1, I2, and I3 respectively represent the peak intensities of the diffraction peaks at 26.7-27.1°, 28.4-28.8°, and 30.4-30.8° in the XRD spectrum of the zinc sulfide material obtained by XRD measurement. That is, I1 represents the peak intensity of the diffraction peak at 2θ=26.7-27.1° in the XRD spectrum of the zinc sulfide material, I2 represents the peak intensity of the diffraction peak at 2θ=28.4-28.8° in the XRD spectrum of the zinc sulfide material, and I3 represents the peak intensity of the diffraction peak at 2θ=30.4-30.8° in the XRD spectrum of the zinc sulfide material.

[0014] In the XRD spectrum of zinc sulfide materials, the diffraction peak of 2θ=26.7~27.1° usually reflects the (100) crystal plane, the diffraction peak of 2θ=28.4~28.8° reflects the (111) crystal plane, and the diffraction peak of 2θ=30.4~30.8° reflects the (200) crystal plane.

[0015] The zinc sulfide material of the present invention has a crystal structure in which a wurtzite structure (also known as a hexagonal crystal structure) and a sphalerite structure (also known as a cubic crystal structure) coexist. The diffraction peak at 2θ=28.4-28.8° is a characteristic peak of the cubic crystal structure, and the diffraction peak at 2θ=26.7-27.1° and the diffraction peak at 2θ=30.4-30.8° are characteristic peaks of the hexagonal crystal structure.

[0016] The present invention has found that due to the difference in crystal structure, the performance effects of zinc sulfide with wurtzite structure and zinc sulfide with sphalerite structure in terms of friction and lubrication are somewhat different. Zinc sulfide with wurtzite structure is usually more wear-resistant than zinc sulfide with sphalerite structure; zinc sulfide with sphalerite structure may provide better lubrication performance; a specific content of zinc sulfide with sphalerite structure can also help improve the friction coefficient of the brake pad material in the high-temperature and high-speed section. When I1, I2, and I3 are controlled at the same time to satisfy the relationship, the crystal structure of the zinc sulfide material is suitable, and the proportion of zinc sulfide with wurtzite structure and sphalerite structure is appropriate, which can enable the friction material to maintain stable friction performance in extreme environments such as low temperature and high temperature.

[0017] The span is the span value of the particle size distribution of the zinc sulfide material. The particle size distribution of the zinc sulfide material affects its surface characteristics and the interaction between particles, thereby affecting the lubrication and friction properties of the zinc sulfide material.

[0018] The present invention comprehensively regulates the particle size distribution span value and crystal structure of the zinc sulfide material, and finds that there should be a certain matching between the span and its crystal structure. When the span is adapted to the crystal structure of zinc sulfide, the interaction between particles can be optimized, and the advantageous characteristics of zinc sulfide with a specific crystal structure can be enhanced, thereby greatly improving the friction performance stability and friction loss of the zinc sulfide material.

[0019] When the zinc sulfide material satisfies 0.2≤span×((I1+I3) / I2)≤6.3, the friction material containing the zinc sulfide material has a low rate of change of friction coefficient at high and low temperatures, and has low friction loss, and the friction stability is significantly improved. When the value of span×((I1+I3) / I2) exceeds the upper limit of the technical solution of the present invention or is lower than the lower limit, the friction material containing the zinc sulfide material has a large rate of change of friction coefficient at high and low temperatures, because the span value of the zinc sulfide particle size distribution is difficult to effectively match with the crystal structure, and the wear condition at high temperatures is also poor due to poor material stability.

[0020] Preferably, the zinc sulfide material satisfies the following relationship: 1.8≤span×((I1+I3) / I2)≤4.0.

[0021] When span×((I1+I3) / I2) satisfies 1.8~4.0, the friction performance stability and friction loss of the friction material containing the zinc sulfide material are relatively better.

[0022] Preferably, the zinc sulfide material satisfies the following relationship: I1 / I3≥1.5.

[0023] More preferably, the zinc sulfide material satisfies the following relationship: 1.7≤I1 / I3≤4.3.

[0024] Preferably, the zinc sulfide material satisfies the following relationship: 0.4≤I4 / I2≤2.0;

[0025] Wherein, the I4 represents the peak intensity of the diffraction peak located at the position of 47.4-47.8° in the XRD spectrum obtained by XRD measurement of the zinc sulfide material.

[0026] The I4 represents the peak intensity of the diffraction peak at 2θ=47.4~47.8° in the XRD spectrum of the zinc sulfide material. The diffraction peak at 2θ=47.4~47.8° usually reflects the (220) crystal plane.

[0027] The ratio of I1 to I3 and the ratio of I4 to I2 both reflect the crystal orientation ratio of zinc sulfide materials. Different crystal planes represent planes intercepted along different crystal axis directions of zinc sulfide materials. Since the surface energy of different crystal planes is different, the size of the surface energy will affect the adsorption capacity of the surface and the interaction with other substances, thereby affecting the friction and lubrication properties. In addition, the stability of different crystal planes is different. Especially in low temperature environments, the crystal structure may change, and different crystal planes may respond differently to temperature changes, resulting in changes in their surface energy or mechanical properties.

[0028] The present invention has found that when I1 / I3 and I4 / I2 meet the above preferred ranges, the zinc sulfide material has better performance at low temperatures and has higher friction performance stability when used in friction materials.

[0029] For zinc sulfide materials, I1, I2, I3, and I4 are related to their crystal structure characteristics, and the crystal structure of zinc sulfide can be adjusted by conventional technical means to change I1, I2, I3, and I4 of the zinc sulfide material. For example, by adjusting the synthetic raw materials, synthetic reaction conditions, and calcination conditions of zinc sulfide, the crystal growth direction and growth rate of zinc sulfide can be controlled, or the crystallization rate, crystallization degree, and recrystallization of zinc sulfide can be controlled to obtain zinc sulfide materials with different crystal structures.

[0030] Preferably, the span ranges from 2.2 to 3.5.

[0031] Span represents (Dv90-Dv10) / Dv50, wherein Dv10, Dv50, and Dv90 represent the particle sizes corresponding to when the volume cumulative distribution percentage of the zinc sulfide material reaches 10%, 50%, and 90%, respectively, and the unit is nm.

[0032] The present invention does not limit the detection methods of Dv10, Dv50 and Dv90. Those skilled in the art can detect the particle size distribution of zinc sulfide materials according to conventional technical means. For example, the particle size distribution laser diffraction method according to GB / T19077-2016 can be referred to and measured using a laser particle size analyzer, such as the OMEC LS-POP (9) laser particle size analyzer.

[0033] A smaller span means that the size distribution of zinc sulfide particles is more uniform, which helps to form a uniform lubricating film on the friction surface and improve the lubrication effect; zinc sulfide with a smaller span also helps to increase the contact area between it and other components in the friction material, interact more, and improve the overall performance of the friction material. However, the span of zinc sulfide material should not be too low. When the span is too low, that is, the particle size distribution of zinc sulfide material is too concentrated, the particle size variation range is small, which may reduce the adaptability of zinc sulfide particles under different stress and temperature conditions. In special environments, zinc sulfide with relatively uniform particle size may not be able to fully adapt to changes in external conditions, thereby affecting friction performance.

[0034] Preferably, the Dv50 of the zinc sulfide material is 550-850nm. Within the above Dv50 range, the particle size of the zinc sulfide material is within an appropriate range, the overall particle size of the zinc sulfide material is not too large or too small, it can be well dispersed when added to the friction material, and has a good interface contact effect with other components in the friction material, which promotes the zinc sulfide material to effectively play its role in improving friction and lubrication performance.

[0035] For the Dv50 and span value of the zinc sulfide material, the zinc sulfide material with a specific particle size distribution can be obtained by crushing and screening the zinc sulfide material, or by selecting a commercially available zinc sulfide material with a suitable particle size.

[0036] Preferably, the loss on ignition of the zinc sulfide material after heating at 950° C. for 3 h is 16.8-18.2%.

[0037] The loss on ignition of zinc sulfide materials is related to many factors, and the value of the loss on ignition is particularly related to the crystal structure stability of the zinc sulfide material. The present invention has found that under the condition of heating at 950°C for 3h, the loss on ignition is 16.8~18.2%, indicating that the zinc sulfide material has a suitable crystal structure stability, which helps the friction performance of the friction material containing the zinc sulfide material to be highly stable. The loss on ignition should not be too low. When the loss on ignition is too low, it may mean that the zinc sulfide material has too high hardness or brittleness, which in turn leads to increased friction loss, especially decreased friction performance at low temperatures. In addition, zinc sulfide may undergo certain state changes at high temperatures to compensate for the performance loss of the resin in the brake material at high temperatures. If the loss on ignition is too low, it will also cause zinc sulfide to be difficult to effectively compensate for the performance loss of the resin, thereby reducing the friction coefficient of the friction material.

[0038] In addition to being affected by the stability of the crystal structure, the loss on ignition of zinc sulfide materials is also affected by the particle size of the zinc sulfide material, that is, the particle size distribution, which will also affect the heating conditions of the zinc sulfide particles and thus affect the loss on ignition.

[0039] Preferably, in the XRD spectrum obtained by XRD measurement of the zinc sulfide material, the half-width at half-height of the diffraction peak at the position of 28.4-28.8° is 0.16-0.30.

[0040] More preferably, in the XRD spectrum obtained by XRD measurement of the zinc sulfide material, the half-width at half-height of the diffraction peak at the position of 28.4-28.8° is 0.18-0.295.

[0041] The half-width of the diffraction peak in the XRD spectrum reflects the degree of defects and crystallinity in the crystal structure of the zinc sulfide material. A relatively small half-width of the diffraction peak indicates that the corresponding crystal structure of the zinc sulfide material has fewer defects and a higher degree of crystallinity, which may reflect the higher crystal stability of the zinc sulfide material. However, the half-width of the diffraction peak should not be too low. The present invention has found that an appropriate amount of crystal defects may increase the active sites on the surface of the material or improve the affinity of the surface, which may help to improve the lubrication performance of the material. When the half-width of the diffraction peak is too low, it will lead to an increase in the friction loss of the friction material containing the zinc sulfide material.

[0042] In a second aspect of the present invention, the present invention provides use of metal sulfide in preparing friction material.

[0043] Specifically, the friction material may be a brake pad.

[0044] In a third aspect of the present invention, the present invention provides a friction material comprising 1 to 20 wt.% of the above-mentioned metal sulfide.

[0045] The friction material may further include a binder and a reinforcing material.

[0046] The binder can be selected from common binders in friction materials, such as at least one of phenolic resin, modified phenolic resin, and silicone modified resin.

[0047] The reinforcing material can be selected from common reinforcing materials in friction materials, such as at least one of mineral fiber, steel fiber, carbon fiber, ceramic fiber, silicon nitride whisker, boride whisker, graphite, barium sulfate, mica powder, and calcium silicate.

[0048] The beneficial effects of the present invention are:

[0049] The present invention provides a metal sulfide. By controlling the particle size distribution span value and the crystal structure of the metal sulfide, the metal sulfide is applied to a friction material. The friction material can maintain stable braking performance under extreme environments such as low temperature and high temperature. The friction coefficient under high temperature and low temperature conditions has a smaller change rate than that under conventional use temperature conditions, and the friction loss is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is the XRD spectrum of the zinc sulfide material prepared in Example 1 of the present application.

[0051] Figure 2 This is the XRD spectrum of the zinc sulfide material prepared in Example 2 of the present application.

[0052] Figure 3 This is the XRD spectrum of the zinc sulfide material prepared in Example 11 of the present application. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0055] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0056] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0057] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0058] Unless otherwise specified, a certain component in the parallel embodiments and comparative examples of the present invention is the same commercially available product.

[0059] Example 1

[0060] Embodiment 1 provides a zinc sulfide material, and the preparation of the zinc sulfide material comprises the following steps:

[0061] S1. Add a zinc source (zinc chloride), a sulfur source (thioacetamide) and a template (diethylenetriamine, DETA) to deionized water, mix well, and obtain a reaction solution; wherein the molar ratio of the zinc source to the sulfur source is controlled to be 1:1;

[0062] S2. The reaction solution was stirred at 300 rpm at 60°C for 2h, then transferred to a reactor and reacted at 280°C for 15h, then taken out and placed at room temperature for cooling, filtering, washing with deionized water, and drying to obtain a pre-product;

[0063] S3. The pre-product was calcined by heating from room temperature to 600°C at a rate of 15°C / min for 2h, then heating to 850°C at a rate of 15°C / min and calcining for 30min;

[0064] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0065] Example 2

[0066] Example 2 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0067] In step S3, the pre-product is calcined according to the following conditions: the temperature is raised from room temperature to 650°C at a rate of 12°C / min for 1.5h, and then the temperature is raised to 700°C at a rate of 12°C / min for 60min;

[0068] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0069] Example 3

[0070] Example 3 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0071] Step S2 is: stirring the reaction solution obtained in S1 at 80°C and 180 rpm for 2 hours, then transferring it to a reactor and reacting it at 200°C for 10 hours, and then reacting it at 300°C for 2 hours; taking it out and cooling it at room temperature, filtering it, washing it with deionized water, and drying it to obtain a pre-product;

[0072] In step S3, the pre-product is calcined according to the following conditions: the temperature is raised from room temperature to 800°C at a rate of 10°C / min and calcined for 2h;

[0073] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0074] Example 4

[0075] Example 4 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0076] In step S3, the pre-product is calcined according to the following conditions: the temperature is raised from room temperature to 500°C at a rate of 10°C / min for 3h, and then the temperature is raised to 900°C at a rate of 15°C / min for 60min;

[0077] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0078] Example 5

[0079] Example 5 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0080] Step S3 comprises the following steps: calcining the pre-product under the following conditions: heating from room temperature to 680°C at a rate of 8°C / min for 2h, then heating to 800°C at a rate of 12°C / min for 45min; taking out and rapidly immersing in deionized water for 60s, taking out and placing at room temperature to cool, washing with deionized water three times, filtering, drying, crushing and sieving to obtain span and D as described in Table 1 v 50% zinc sulfide material.

[0081] Example 6

[0082] Example 6 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0083] In step S3, the pre-product is calcined according to the following conditions: the temperature is raised from room temperature to 800°C at a rate of 15°C / min for 4h, and then the temperature is raised to 950°C at a rate of 8°C / min for another 30min;

[0084] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0085] Example 7

[0086] Example 7 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0087] In step S3, the pre-product is calcined under the following conditions: the temperature is raised from room temperature to 450°C at a rate of 10°C / min for 2.5h, and then the temperature is raised to 800°C at a rate of 10°C / min for 30min;

[0088] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0089] Example 8

[0090] Example 8 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0091] In step S2, the reaction solution was stirred at 80°C and 1000 rpm for 3 h, and then transferred to a reactor and reacted at 200°C for 10 h;

[0092] In step S3, the pre-product is calcined according to the following conditions: the temperature is raised from room temperature to 900°C at a rate of 15°C / min and calcined for 4h;

[0093] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0094] Example 9

[0095] Example 9 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0096] In step S3, the pre-product is calcined according to the following conditions: the temperature is raised from room temperature to 500°C at a rate of 5°C / min for 3h, and then the temperature is raised to 900°C at a rate of 10°C / min and calcined for 120min;

[0097] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0098] Example 10

[0099] Example 10 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0100] Step S2 is: stirring the reaction solution obtained in S1 at 45°C and 60 rpm for 10 hours, and then stirring at 80°C and 60 rpm for 4 hours; then transferring the mixture to a reactor and reacting it at 180°C for 20 hours; taking it out and cooling it at room temperature, filtering it, washing it with deionized water, and drying it to obtain a pre-product;

[0101] In step S3, the product calcined under the same calcination conditions as in Example 1 was crushed and sieved to obtain span and D as shown in Table 1. v 50% zinc sulfide material.

[0102] Embodiment 11

[0103] Example 11 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0104] Step S2 is: stirring the reaction solution obtained in S1 at 60° C. and 30 rpm for 8 h, and then stirring at 80° C. and 30 rpm for 8 h; then transferring the reaction solution to a reactor and reacting it at 200° C. for 18 h; taking it out and cooling it at room temperature, filtering it, washing it with deionized water, and drying it to obtain a pre-product;

[0105] In step S3, the product calcined under the same calcination conditions as in Example 1 was crushed and sieved to obtain span and D as shown in Table 1.v 50% zinc sulfide material.

[0106] Comparative Example 1

[0107] Comparative Example 1 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0108] In step S3, the pre-product was calcined under the following conditions: the temperature was raised from room temperature to 850°C at a rate of 20°C / min for 6 hours; after being taken out, it was quickly immersed in deionized water for 30 seconds, and after being taken out, it was placed at room temperature for cooling, washed with deionized water three times, filtered, dried, crushed and sieved to obtain span and D as described in Table 1. v 50% zinc sulfide material.

[0109] Comparative Example 2

[0110] Comparative Example 2 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0111] In step S3, the pre-product is calcined under the following conditions: the temperature is increased from room temperature to 800°C at a rate of 8°C / min for 1 hour, then the temperature is increased to 900°C at a rate of 10°C / min for further calcination for 30 minutes, then the temperature is decreased to 600°C at a rate of 10°C / min for further calcination for 1 hour;

[0112] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0113] Comparative Example 3

[0114] Comparative Example 3 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0115] In step S2, the reaction solution is stirred at 80 rpm at 50° C. for 2 h, then transferred to a reactor and reacted at 300° C. for 8 h, taken out and placed at room temperature for cooling, filtering, washing with deionized water, and drying to obtain a pre-product;

[0116] In step S3, the pre-product is calcined according to the following conditions: the temperature is raised from room temperature to 700°C at a rate of 15°C / min for 1.5h, and then the temperature is raised to 850°C at a rate of 15°C / min for another 2.5h;

[0117] After cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 were obtained. v 50% zinc sulfide material.

[0118] Comparative Example 4

[0119] Comparative Example 4 provides a zinc sulfide material. The preparation method of the zinc sulfide material is similar to that of Example 1, except that:

[0120] In step S3, the pre-product is calcined: the temperature is raised from room temperature to 800°C at a rate of 10°C / min, wherein the temperature is kept constant for 30min at 500°C, 600°C, and 700°C, and the temperature is kept constant for 3h at 800°C; after cooling at room temperature, washing with deionized water three times, filtering, drying, crushing and sieving, the span and D as described in Table 1 are obtained. v 50% zinc sulfide material.

[0121] The prepared zinc sulfide material was subjected to XRD test, and the half-height width (FWHM) of the diffraction peak at the position of 28.4-28.8°, I1, I2, I3, I4, and I4 were measured respectively. WHM2 ), calculate the values ​​of (I1+I3) / I2, I1 / I3, I4 / I2;

[0122] The conditions of the XRD test are: tested using an X-ray diffractometer, Cu-Kα rays, scanning range 15~80°, PEAK: 21-pts / Parabolic Filter, Threshold=3.0, Cutoff=0.1%, BG=3 / 1.0, Peak-Top=Summi.

[0123] The zinc sulfide material prepared above was tested for loss on ignition, and the test conditions were as follows: take a certain amount of zinc sulfide and accurately weigh its mass as m1; heat the zinc sulfide material at 950°C for 3 hours in an air atmosphere, cool to room temperature, and accurately weigh its mass again as m2; calculate the loss on ignition = (m1-m2) / m1*100%.

[0124] Specifically, the relevant test results and particle size distribution of the zinc sulfide materials of the embodiment and the comparative example are shown in Table 1. The XRD spectrum of the zinc sulfide material of Example 1 is shown in Figure 1 As shown, I1 is 4449, I2 is 6068, I3 is 1964, and I4 is 4524; the XRD spectrum of the zinc sulfide material of Example 2 is as shown Figure 2 As shown, I1 is 5496, I2 is 6319, I3 is 3239, and I4 is 4910; the XRD spectrum of the zinc sulfide material of Example 11 is as shown Figure 3 As shown, I1 is 11696, I2 is 6819, I3 is 1913, and I4 is 12746.

[0125] Table 1

[0126]

[0127] After calculation, the formulas satisfied by each embodiment and comparative example are shown in Table 2-1, Table 2-2 and Table 2-3.

[0128] The zinc sulfide materials prepared in the embodiments and comparative examples were used to prepare friction materials according to the following component contents (weight percentage):

[0129] Phenolic resin (Kun Yi Resin Materials Company, KT-3640CRA) 20wt.%, aramid fiber 15wt.%, basalt fiber 25wt.%, filler (mica powder and calcium silicate mixed in a weight ratio of 1:1) 30wt.%, zinc sulfide material 10wt.%.

[0130] The preparation method of the friction material is as follows:

[0131] The friction material is obtained by mixing phenolic resin, aramid fiber, basalt fiber, filler and zinc sulfide material, hot pressing (temperature 180°C, pressure 25MPa, time 8 minutes), and heat treating (temperature 150°C, heat treating time 12 hours).

[0132] The friction performance of the friction material is tested. The specific method of testing is as follows:

[0133] The friction coefficient and wear rate of the friction material were tested using a high and low temperature friction and wear tester from Fuller Instrument Technology (Shanghai) Co., Ltd. The test sample of the friction material was cut into a cuboid of 30mm×30mm×8mm, and the disc-block contact form was adopted. The material of the mating piece was gray cast iron. The test condition selected 0.8MPa as the test load point, the disc speed was selected as 500r / min, the test temperatures of the friction coefficient were -20℃, 200℃, and 500℃, and the test temperatures of the wear rate were -20℃ and 500℃. Each group of samples was tested 10 times in parallel and the average value was recorded.

[0134] The friction coefficients measured at -20℃, 200℃, and 500℃ are recorded as μ1, μ0, and μ2, respectively. The change rate of friction coefficient at low temperature is calculated to be (μ0-μ1) / μ0×100%, and the change rate of friction coefficient at high temperature is calculated to be (μ0-μ2) / μ0×100%;

[0135] The wear rates measured at -20℃ and 500℃ are respectively recorded as W -20 , W 500 , the unit of measurement is: ×10 -7 cm 3 / (N·m).

[0136] The test results are shown in Table 2-1, Table 2-2 and Table 2-3.

[0137] Table 2-1

[0138]

[0139] Table 2-2

[0140]

[0141] Table 2-3

[0142]

[0143] It can be seen from Table 2-1, Table 2-2 and Table 2-3 that the zinc sulfide materials prepared in various embodiments of the present invention are applied to friction materials, which can effectively improve the friction coefficient change rate of the friction material, so that the friction coefficient change rate of the friction material at high temperature is ≤12.1%, and the friction coefficient change rate at low temperature is ≤20.3%, and the wear rate of the friction material at high and low temperatures is ≤0.35.

[0144] According to Examples 1 to 6, it can be seen that when the zinc sulfide material further satisfies I1 / I3≥1.5 and / or 0.4≤I4 / I2≤2.0, the friction coefficient change rate of the friction material is relatively lower, especially at low temperatures, the friction coefficient change rate is significantly improved.

[0145] According to Examples 1-3 and 7-8, it can be seen that when the span of the zinc sulfide material is within an appropriate range, the friction material can have both a good friction coefficient change rate and a low wear rate.

[0146] According to Examples 9 to 11, it can be seen that when the loss on ignition of the zinc sulfide material is too high, it may mean that the crystal structure of the zinc sulfide material is not suitable, resulting in increased friction loss at high temperatures and a higher rate of change of the friction coefficient at high temperatures; when the loss on ignition of the zinc sulfide material is too low, the friction material not only increases friction loss, but also has a larger rate of change of the friction coefficient at low temperatures.

[0147] In the comparative example, when the span×((I1+I3) / I2) value of the zinc sulfide material exceeds the range of 0.2~6.3, not only is the friction coefficient changing rate too large at high and low temperatures, but also the wear rate is very high at high temperatures due to the poor stability of the material.

[0148] It should be noted that the amount of zinc sulfide material added can be adjusted according to the needs of the friction material. Optionally, the zinc sulfide material can be added in the friction material at 1-20wt.%.

[0149] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A metal sulfide, characterized in that: The metal sulfide is a zinc sulfide material, and the zinc sulfide material satisfies the following relationship: 0.2≤span×((I1+I3) / I2)≤6.3; Wherein, the span is the particle size distribution span value of the zinc sulfide material; span represents (Dv90-Dv10) / Dv50, wherein Dv10, Dv50, and Dv90 represent the particle sizes corresponding to when the volume cumulative distribution percentage of the zinc sulfide material reaches 10%, 50%, and 90%, respectively, and the unit is nm; The I1, I2, and I3 respectively represent the peak intensities of the diffraction peaks at the positions of 26.7-27.1°, 28.4-28.8°, and 30.4-30.8° in the XRD spectrum of the zinc sulfide material obtained by XRD measurement.

2. The metal sulfide according to claim 1, characterized in that: The zinc sulfide material satisfies the following relationship: 1.8≤span×((I1+I3) / I2)≤4.

0.

3. The metal sulfide according to claim 1 or 2, characterized in that: The zinc sulfide material satisfies the following relationship: I1 / I3≥1.

5.

4. The metal sulfide according to claim 1 or 2, characterized in that: The zinc sulfide material satisfies the following relationship: 1.7≤I1 / I3≤4.

3.

5. The metal sulfide according to claim 1 or 2, characterized in that: The zinc sulfide material satisfies the following relationship: 0.4≤I4 / I2≤2.0; wherein I4 represents the peak intensity of the diffraction peak at the position of 47.4-47.8° in the XRD spectrum obtained by XRD measurement of the zinc sulfide material.

6. The metal sulfide according to claim 1, characterized in that: The span ranges from 2.2 to 3.

5.

7. The metal sulfide according to claim 1, characterized in that: The Dv50 of the zinc sulfide material is 550-850nm.

8. The metal sulfide according to claim 1, characterized in that: The ignition loss of the zinc sulfide material after heating at 950° C. for 3 hours is 16.8-18.2% by mass.

9. Use of the metal sulfide according to any one of claims 1 to 8 in the preparation of friction materials.

10. The use according to claim 9, characterized in that: The friction material is a brake pad.

11. A friction material, characterized in that: Comprising 1 to 20 wt.% of the metal sulfide according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Friction material for brakes

    CN102713334B

  • Wear-resistant brake pad and preparation method thereof

    CN103644228A

  • Core / shell type wurtzite / blende ZnS hetero nano structure and preparation method thereof

    CN101901827A

  • Ultrasonic / microwave synergistic constant-pressure solvothermal synthesis method of cubic-structure and hexagonal-structure nano ZnS semiconductor material

    CN102923760A